Are Audit Firms' Compensation Policies Associated with Audit Quality? - Ernstberger, Jürgen; Koch, Christopher; Schreiber, Eva Maria; Trompeter, Greg (Contemporary Accounting Research, 2020)
ABSTRACT We examine how compensation policies of audit firms are associated with audit quality. Specifically, we investigate the effects of the ratio of variable to fixed compensation and the size of the basis for profit sharing (i.e., whether partners share profits in a small or in a large profit pool). For our analyses, we use detailed mandatory disclosure of the compensation policies in German audit firms. We document that compensation policies vary considerably across audit firms. We find that profit sharing in a small profit pool and high variable compensation are two characteristics of auditor compensation associated with lower audit quality. We also find some evidence suggesting that audit quality may be most at risk in cases in which partners rely more heavily on variable compensation to divide a relatively small profit pool. In additional analyses, we find that these associations are more pronounced in medium‐sized audit firms. We argue that this finding may result from these firms being too large for audit partners to directly monitor each other effectively, yet simultaneously too small to have sophisticated centralized monitoring systems in place. Finally, we find that integrating partner‐specific, nonprofit‐related performance metrics into the compensation structure mitigates the adverse effects of small profit pools and high variable compensation.